Strategies for the Path Selection in a DWDM Optical Network Operating with All-Optical Wideband Wavelength Converters - Fagotto, Eric A. M.; Abbade, Marcelo L. F. [UNESP]; Forghani-Elahabad, Majid; Davoli, Gianluca; Pittalà, G. Francesco; Raffaelli, Carla; Callegati, Franco; Bonani, Luiz H. (Institute of Electrical and Electronics Engineers (IEEE), 2025)
This paper evaluates path selection strategies for DWDM optical networks operating with All-Optical Wideband Wavelength Converters (AOWWCs). We compare four heuristics against a cost-based algorithm with converter placement constraints in a dynamic traffic scenario. Results show that some heuristics achieve blocking ratios comparable to the cost-based approach while offering lower computational complexity. These findings highlight the potential of heuristic methods to improve network performance and AOWWC efficiency without incurring high costs.